The Structure of Project Teams Facing Differentiated Environments: An Exploratory Study in Public Accounting Firms. - Watson, David J. H. (The Accounting Review, 1975)
Abstract The fundamental importance and relevance of the behavioral sciences to accounting is exemplified by the number of recent behaviorally oriented accounting research studies, as of April 1975. A subset of these studies has been concerned with organizational and social psychological aspects of accounting firms. These studies seem to have the potential for contributing to both the accounting profession and the behavioral sciences. Within this trend, the purpose of this article is to explore the organization of public accounting firms using a behavioral science theory of organization. An organization can be modeled as a cycle consisting of three basic units, namely, an input unit, a transformation process, and lastly, an output unit. An audit engagement is not a completely standardized input. Different client organizations have different accounting systems. Accounting systems either are tailored to an organization or they evolve as the organization evolves. Consequently, each accounting system has some idiosyncracies representing the particular characteristics and information requirements of the organization.